UNIFIED BASIC SOFTWARE AND HARDWARE COMPLEX FOR PRECISION ENERGY-SAVING SYSTEMS OF AUTOMATIC REGULATION AND CONTROL - Kaniuk, G. I.; Mezeria, A. Yu.; Knіazіeva, V. N.; Кhoroshun, D. M.; Fursova, T. N. (Radio Electronics, Computer Science, Control, 2019)
Context. Methods for the synthesis of precision electro-hydraulic control systems using the principle of multiplication are proposed. Use of the principle of multiplication allows to create compact control systems of technological objects, having high rates of precision and operation speed. The problem of creating the unified basic software and hardware complex for precision automatic control systems and control of an optional technological object is considered. On the basis of effective methods of the modern theory of optimal control, control algorithms have been developed that provide maximum compensation for all types of statistical and dynamic control errors. Objective. The urgency of the work is due to the need to improve the precision of control systems of technological objects and the development of software and hardware complex for these systems. Method. We have used the methods of optimal control, methods of structural synthesis. To confirm the validity of the developed models and principles, the method of experimental studies based on the operating equipment of test benches was used. To debug an experimental model of a basic software and hardware complex for testing the plain bearings of internal combustion engines, mathematical simulation of an electro-hydraulic drive was used. For the synthesis of a precision controller, the multiplication method was used. Results. A number of standard sizes of high-speed precision EHSS based on part-turn hydraulic motors with a torque moment of up to 40 kNm were developed, providing reproduction in the tracking mode of specified input effects with a bandwidth of up to 20 Hz, positioning accuracy of up to one angular minute and a control range of up to 104. Based on developed EHSS automated simulation dynamic stands were created and brought to practical use for testing mobile object guidance systems (Customer-Central Research Institute of Chemistry and Mechanics, Moscow) and the semi-axes transmission (Customer-JSC “КАМАZ”, Naberezhnye Chelny). Based on the results of the research, a basic software and hardware complex for testing equipment of agricultural, automotive and other industries was created. The high-speed precision regulator for controlling the position of steam turbine actuator valves has been synthesized to compensate for all the main types of static and dynamic errors and more than double the performance compared to the base variant while maintaining acceptable stability margins (the results are used in promising projects of the State Energy Company “Centrenergo”, National Nuclear Energy Generating Company “Energoatom”, as well as in the Institute of Control Problems of the National Academy of Sciences of Ukraine. Conclusions. The practical engineering methods for the synthesis of effective control laws of precision electro-hydraulic systems are proposed, as well as a number of effective regulators providing high characteristics of precision and operation speed. The principle of multiplicative control is proposed which allows to synthesize effective control algorithms for individual, autonomous, fully controlled and observable electro-hydraulic servo drive circuits based on third-order mathematical models. For selected autonomous control loops, effective control laws are obtained based on modal control methods and solving inverse problems of dynamics. The proposed synthesis techniques are considered using the harmonic linearization method, the real nonlinear characteristics of the control signal power limitation, which allows determining the real rational ratios of the regulator parameters and real limiting precision and speed indicators, as well as preventing unwanted auto-oscillatory modes in the systems. In order to reduce the number of measured parameters used in the formation of the proposed control laws, on the basis of the well-known general principles of the synthesis of observing identification devices, the universal structures and formulas for calculating the parameters of standard models of autonomous control circuits of the EHSS were obtained. The method of autonomous testing and debugging of the EHSS control system using the electronic simulator of electro-hydraulic actuator has been improved which makes it possible to significantly reduce the time and cost involved in creating and engineering development a complex system.